UPAYA PENGENDALIAN ALIH FUNGSI LAHAN SAWAH UNTUK PELESTARIAN SUBAK DAN KEBERLANJUTAN PERTANIAN DI BALIÃ¢â‚¬Â - Budiasa, Wayan (dwijenAGRO, 2011)
One of important elements of Tri Hita Karana in subak system within BaliÂ  is a rice field compound with clearly natural boundaries and irrigation facilities. If the entire rice fields are functionally converted, this could be definitely said that subak systemÂ  would be disappear. The rice field conversion is very fast and has threated the subak existence. Considering subak is one of the cultural resources and as a Bali sustainability point, it should be endeavored to control the rice field conversionÂ  in order to ensure the agricultural sustainability and subak itself.Key words: Conversion of rice fields, subak, agriculture and sustainability.Â